HCV test&treat in Milan prisons-an effective strategy for microelimination and health gaps reduction. (13th November 2019) - Casigliani, V; Giuliani, R; Sebastiani, T; Arzilli, G; Scardina, G; Tavoschi, L; Ranieri, R
Abstract: Background: People in prison represent a high-risk population for HCV infection control due the overrepresentation of people with a history of intravenous drug use, psychiatric patients and other vulnerable populations who have often reduced access to healthcare. With the advent of new direct antiviral agents (DAAs) HCV micro-elimination in prison setting became a feasible strategy. Methods: We conducted in 2017 and 2018 a cross-sectional evaluation of HCV treatment cascade in one detention prison, Opera (OP), and one pre-trial detention center, San Vittore (SV) in Milan. A dedicated protocol for HCV eligibility and care was applied. We collected data on demographics, HCV testing and treatment on all inmates on October 31st 2017 and 2018. Data collection ended on December 31st of each year. Results: On October 31st 2017, 2366 inmates were living in the two facilities, 2369 in 2018, of these, 1036 (43, 7%) were already present in 2017 (71, 3% in OP; 28, 7% in SV). In both years the majority were men (95.4%; 96, 4%) with a median age of 41 years and Italians (57%; 61, 9%). Prevalence of reported drug use remained high (46, 5%; 44, 2%). HCV screening coverage was 89% in both years, while HCV-RNA test coverage increased (90, 6%; 99%). HCV Ab+ was stable (212, 10.1%; 194, 9, 2%). At the end of 2017 and 2018, 106 (50%) and 117 (60, 3%) started treatment eligibility process of which 90 (42, 4%) and 106 (54, 6%) completed DAAs in prison. Considering last available viremia, 41 inmates (19, 3%) were viremic in 2017 (OP 16.1%; SV 24, 4%), while only 13 inmates (6, 7%) in 2018 (OP < 1%, SV 15, 4%). On December 31st 2018, among HCV Ab+ detainees 122 (62, 9%) were never linked to care before incarceration. Conclusions: Our study shows the success of the HCV testing and treatment strategy to achieve HCV micro-elimination in a prison setting with a significant drop in the pool of viremic individuals. We highlight how prison health care may represent a unique point of access for vulnerable population. Key messages: HCV micro-elimination is a feasible and effective strategy in prison settings. High-quality healthcare in prison contributes to reduce health gaps and improve access for socially deprived population.